Analisis Strategi Pemasaran Telur Itik di Desa Teluk Baru Kecamatan Amuntai Selatan Kabupaten Hulu Sungai Utara Propinsi Kalimantan Selatan - Arief Hidayatullah; Purna Kusumayana; Munatun Najah (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2019)
This study aims to determine the strengths, weaknesses, opportunities and threats in the marketing of duck eggs in the Teluk Baru Village Amuntai Selatan Kabupaten Hulu Sungai Utara Regency Kalimantan Selatan Province. Results of research conducted in the Teluk Baru Kecamatan Amuntai Selatan District Hulu Sungai Utara Regency Kalimantan Selatan Provinve to the marketing of duck eggs using the formulation and selection strategy is based on the analysis of internal and external environments using IFE and EFE matrix, the values obtained from the analysis of external factors (EFE) of 2.967, and for the value of the analysis of internal factors (IFE) of 2.98. It can be concluded that the marketing of duck eggs in North Hulu Sungai is medium. Marketing the placement of duck eggs is in cell V with a strategy to hold and maintain. The main types of strategies that can be applied are intensive strategies, market penetration strategies, product development.